LEGAL REGULATION OF IMPLEMENTATION OF ECOLOGICAL CONTROL OF A SUBJECT OF AGRICULTURAL SECTOR OF ECONOMY - Мілімко, Лариса Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: to consider the problems of legal regulation of environmental control of agricultural entities in Ukraine in connection with which to establish prospects for its development, formulate an author’s definition of environmental control of agricultural entities, outline the circle of entities engaged in state environmental control, the problems of their proper performance of their functions. Methods: the study was conducted using methods such as analysis, synthesis, comparison. The results formulated the author’s definition of the concept of environmental control of the subjects of the agricultural sector of the economy, the established bodies that implement it and the specifics of implementation in connection with the reformation processes. Discussion: of the problem of environmental control of entities of the agricultural sector of the economy. Having come to the realization that the ecological situation in Ukraine is catastrophic, nowadays the legislative base is being formed at a more accelerated pace and new mechanisms of environmental control are being introduced. However, to a large extent, the question of the legal fixing of the goals and methods of such control has not yet passed from the scientific-theoretical plane to the practical one. The concept of ecological control of agricultural sector entities should be understood as the activity of authorized entities that check compliance with and enforceable environmental legislation in the field of environmental protection, use of natural resources and ensure environmental safety in the process of production, harvesting and sale of agricultural products. Ukraine has established a system of legal acts that regulate relations on environmental controls, but they need improvement. An extensive system of government bodies performing relevant control functions also needs to be improved, first and foremost, in the direction of differentiating control functions between them in the environmental sphere. The introduction of an integrated automated system «Ecological control» will have a positive impact on the compliance of environmental legislation by the actors of the agrarian sector of the economy.